A New Deal for Refugees: How Land Restoration and Infrastructure Modernization Can Help Solve the Refugee Crisis - Goldman, Jonas Philip (Consilience, 2017)
The migrant crisis in Europe is the largest since WWII. Millions of migrants are without hope or a source of income. However, this tragedy could present an opportunity for Europe as the EU currently faces two problems, which a large influx of labor could fix. First, decaying outdated European infrastructure and construction and secondly the abandonment of European farmland. During the 1920’s the Civilian Conservation Corps (CCC), a government program from the great depression, employed large numbers of unemployed men in land management fields. Just as the CCC addressed the environmental and social problems of its day, a modern government program modeled after the CCC could address the issues currently facing the EU. This paper lays out a roadmap for just such a program outlining how the EU could employ refugees to address the current environmental issues facing Europe. The paper also explores potential uses for abandoned farmland, such as re-utilization for agriculture, agroforestry and re-wilding as well as the management, funding and potential issues faced by such a program.